Risks of accelerated digitalisation of society during the COVID-19 pandemic: a sociological analysis - Lebedeva Еlena V. (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
The article is devoted to a sociological analysis of the accelerated social digitalisation’s risks in the context of the COVID-19 pandemic. The general role of digital technologies in the modern citizen’s life is described, the most sensitive to the impact of accelerated digitalisation areas (labour, lifestyle, interpersonal communication) are highlighted. Based on the results of an empirical study, possible technical, organisational, emotional and psychological difficulties that citizens face in the process of using digital technologies are indicated. In conclusion, generalised risks of accelerated digitalisation are proposed (reformatting of social connections, the emergence of new social inequality dimensions, information overload and dependence on technology).